Family Meal-Time Interaction: Understanding the Family in its Natural Setting - Larson, Lyle E.; Fraser, Jennefer D. (Canadian Journal of Counselling and Psychotherapy, 2012)
There is growing evidence concerning the value of studying the family in its natural habitat (Kantor and Lehr, 1975) for both understanding and explaining family interaction, as well as facilitating therapeutic intervention (White, 1976). This paper summarizes the existing literature on the importance of the family meal in analyzing family interaction, presents the results of a naturalistic observational study of a normal (non-pathological) family, and identifies the implications of the study for research and therapy.